If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5X + 2(x + -1) = 3x + 4x + 15 Reorder the terms: 5X + 2(-1 + x) = 3x + 4x + 15 5X + (-1 * 2 + x * 2) = 3x + 4x + 15 5X + (-2 + 2x) = 3x + 4x + 15 Reorder the terms: -2 + 5X + 2x = 3x + 4x + 15 Reorder the terms: -2 + 5X + 2x = 15 + 3x + 4x Combine like terms: 3x + 4x = 7x -2 + 5X + 2x = 15 + 7x Solving -2 + 5X + 2x = 15 + 7x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 5X + 2 + 2x = 15 + 2 + 7x Reorder the terms: -2 + 2 + 5X + 2x = 15 + 2 + 7x Combine like terms: -2 + 2 = 0 0 + 5X + 2x = 15 + 2 + 7x 5X + 2x = 15 + 2 + 7x Combine like terms: 15 + 2 = 17 5X + 2x = 17 + 7x Add '-2x' to each side of the equation. 5X + 2x + -2x = 17 + 7x + -2x Combine like terms: 2x + -2x = 0 5X + 0 = 17 + 7x + -2x 5X = 17 + 7x + -2x Combine like terms: 7x + -2x = 5x 5X = 17 + 5x Divide each side by '5'. X = 3.4 + x Simplifying X = 3.4 + x
| -2-3(4-4r)=-50 | | k/1.2=-0.07 | | .333y+11=.5y-3 | | x^2+6x+3=-6 | | 2.3(m)+m=26.4 | | 5=1.6x | | 5(3+5c)=60 | | 7b^2+32b+6=0 | | 57+x=6x+7 | | x^2+2x-101=2x-1 | | 16=c-(-12) | | -28+b=-7(b+4) | | 8k+6+5k=6 | | 8-3=n-13 | | 5d-25+2d=2d | | x+12=32-3x | | x^2+6x-32=2x | | 8-3=-13n | | 4y=24-0 | | x-4-9=0 | | 3X-7=10X+4-7X-11 | | 7(x-3)-(9x+2)=15 | | 10x-5(3x+5)=-10x | | 37-17=4(x-9) | | x^2+18x+75=-6 | | 7x=52 | | -2.1=d+(-9.3) | | 75+4v=150+1v | | 6(x-6)-10= | | a(b-2)=3a+b(a)-5a | | x^2+13=9x-5 | | 21+8y+10m-5y-5m+10= |